1981
DOI: 10.1073/pnas.78.5.3142
|View full text |Cite
|
Sign up to set email alerts
|

An unusual symmetric recombinant between adenovirus type 12 DNA and human cell DNA

Abstract: On purification of human adenovirus type 12 (Adl2) by equilibrium sedimentation in CsCl density gradients, two bands of particles, are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…First, it was documented that after repeated passaging at high moi on permissive cells with different adenovirus serotypes, subgenomic DNA preferentially containing the left end of the virus genome could be packaged into virions and separated from wild-type virions by CsCl density-gradient centrifugation (17). Second, after repeated high moi passage of Adl2 on human KB cells, hybrid viruses containing symmetrically duplicated chromosomal DNA of KB cell line flanked by 700-1150 bp of DNA fragment from the left terminus of Adl2 (SYREC) were produced (18)(19)(20). These SYREC could be separated from Adl2 by a CsCl equilibrium density gradient and also could be propagated over years together with Adl2.…”
Section: Resultsmentioning
confidence: 99%
“…First, it was documented that after repeated passaging at high moi on permissive cells with different adenovirus serotypes, subgenomic DNA preferentially containing the left end of the virus genome could be packaged into virions and separated from wild-type virions by CsCl density-gradient centrifugation (17). Second, after repeated high moi passage of Adl2 on human KB cells, hybrid viruses containing symmetrically duplicated chromosomal DNA of KB cell line flanked by 700-1150 bp of DNA fragment from the left terminus of Adl2 (SYREC) were produced (18)(19)(20). These SYREC could be separated from Adl2 by a CsCl equilibrium density gradient and also could be propagated over years together with Adl2.…”
Section: Resultsmentioning
confidence: 99%
“…4,1984 on May 11, 2018 by guest http://mcb.asm.org/ 308 HANAHAN AND GLUZMAN normal right end. Defective adenoviruses have been isolated and shown to stably persist as large palindromes which contain adenoviral information originating only from the left end (6,7). This indicates that the configuration of left-end sequences on both the left and right ends is favorable under certain conditions.…”
mentioning
confidence: 99%
“…Deuring et al describe an Ad12/cellular DNA chimera (symmetric recombinant 1) that consists almost entirely of cellular DNA flanked by 700-1150 bp of the 5Ј end of the Ad12 genome in a large inverted repeat of the type ABCDDЈCЈBЈAЈ. 19 This construct was stable through serial passage for years. Further analysis of a second construct (symmetric recombinant 2) revealed that 2081 bp of the left terminus of Ad12 were linked directly to cellular DNA.…”
Section: Discussionmentioning
confidence: 99%